Perovskites: Structure and Growth Control of Organic–Inorganic Halide Perovskites for Optoelectronics: From Polycrystalline Films to Single Crystals (Adv. Sci. 4/2016). Issue 4 (April 2016) - Chen, Yani; He, Minhong; Peng, Jiajun; Sun, Yong; Liang, Ziqi
Abstract : In article number 1500392, Z. Liang and co‐workers review the development of structure and growth control of organic–inorganic halide perovskites for optoelectronics, in the forms of polycrystalline films and single crystals ranging from three, two, one, and zero dimensions, ideal platforms for fundamental studies due to the absence of grain boundaries.